Quantitative sensory testing in endometriosis patients with cyclic vs. non-cyclic pain: a case-control study - Dückelmann, Anna M.; Rolke, Roman; Möller, Katharina; Magerl, Walter; Mechsner, Sylvia; Kopf, Andreas (European journal of pain, 2025)
Background Endometriosis is a chronic, inflammatory disease with considerable symptom load in affected female patients. Cyclic pain (associated with menstruation) dominates in most patients, but few patients suffer from persistent non-cyclic pain. This study aims to investigate whether the somatosensory profile in endometriosis differs from healthy controls or between cyclic and non-cyclic subtypes. Moreover, we aimed at potential identifiers of peripheral or central nervous sensitization underpinnings of endometriosis in the QST profile. Methods The standardised investigation protocol for quantitative sensory testing (QST) of the German research network of neuropathic pain was used to find possible differences compared to healthy controls or between cyclic and non-cyclic subtypes of endometriosis potentially providing hints for altered peripheral and central nociceptive processing. Results Endometriosis patients showed significant hyperalgesia to cold and blunt pressure in the affected body area (non-cyclic>cyclic, all p < 0.05), but not pinprick hyperalgesia, dynamic mechanical allodynia or facilitated pain summation (all p > 0.30). Exaggerated pressure hyperalgesia was most pronounced, regionally restricted and present in every patient (p << 0.0001). Higher thermal and tactile detection thresholds indicated non-nociceptive somatosensory loss, which differed only marginally between subgroups. Thermal loss and hyperalgesia to cold, heat and blunt pressure were also identified to a lesser extent in a remote test site (hand dorsum). Conclusions Endometriosis patients exhibited a pattern of somatosensory changes that is consistent with peripheral rather than central sensitization. Primary afferent sensitization facilitating spinal transmission of convergent input from the affected and suprapubic referred pain area is the most likely mechanism of hyperalgesia in endometriosis. Significance Statement Pain and hyperalgesia are amongst the most burdensome features in endometriosis. This QST case-control study in endometriosis patients identifies massive pressure hyperalgesia as the most significant somatosensory alteration in the viscerotome of the lower abdomen, which is easily accessible for testing in patients. This finding highlights the role of peripheral sensitization as the dominant mechanism of endometriosis-related hyperalgesia, which has major implications for future treatment, which may target prevention of peripheral sensitization by suppression of NGF or TRPV1 receptors.
Erstmals veröffentlicht: 5. November 2025
Gesehen am 26.01.2026